2011
DOI: 10.1063/1.3579523
|View full text |Cite
|
Sign up to set email alerts
|

Si nanoparticle–Er3+ coupling through contact in as-deposited nanostructured films

Abstract: Silicon nanoparticle-ZnS nanophosphors for ultraviolet-based white light emitting diode J. Appl. Phys. 112, 074313 (2012) High energy-resolution electron energy-loss spectroscopy study on the near-infrared scattering mechanism of Cs0.33WO3 crystals and nanoparticles J. Appl. Phys. 112, 074308 (2012) Luminescence of free-standing versus matrix-embedded oxide-passivated silicon nanocrystals: The role of matrix-induced strain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…Indeed, with a multilayered structure, population inversion is possible even with an optically active Er 3þ fraction of only 60%, since a multilayer structure mini-mizes concentration quenching while maximizing the nc-Si and Er interaction. These results are consistent with experimental reports on the advantages of such multilayered structure 18,25 and suggests that for nc-Si sensitized Er emission, nano-scale engineering of the structure to ensure close contact of all of the doped Er 3þ with nc-Si should be performed.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, with a multilayered structure, population inversion is possible even with an optically active Er 3þ fraction of only 60%, since a multilayer structure mini-mizes concentration quenching while maximizing the nc-Si and Er interaction. These results are consistent with experimental reports on the advantages of such multilayered structure 18,25 and suggests that for nc-Si sensitized Er emission, nano-scale engineering of the structure to ensure close contact of all of the doped Er 3þ with nc-Si should be performed.…”
supporting
confidence: 90%
“…Indeed, reported values of sensitized fraction ranges from as low as 3% 17 to >50%. 18 In this paper, we report on results of a finite-element, Monte-Carlo simulation of nc-Si sensitization of Er 3þ . By using Monte-Carlo simulation instead of rate equation, it is possible to vary the material structure and composition arbitrarily on sub-nm scale to investigate their effect.…”
mentioning
confidence: 99%
“…Due to unique electrical, photo-optical properties and chemical activity, ZnO nanoparticles have several applications, among others, including: production of catalysts, electrodes for photoelectrochemical cells, gas sensors, ultraviolet filters, and various nanocomposites. There are several methods of obtaining nanoparticles, namely: by thermal decomposition of precursors (salts) in a solid state, Chemical Vapor Deposition (CVD) technique, laser evaporation [1,2], solution deposition or in a solvothermal way from over-saturated salt solutions in various solvents in the precipitated and/or hydrolysis process [3 -5]. In recent times electrochemical methods have often been applied.…”
Section: Introduction *mentioning
confidence: 99%
“…Figure 1 shows a crosssection energy filtered transmission electron microscopy (EFTEM) image of one multilayered a-Si:a-Al 2 O 3 film containing amorphous Si nanostructured layers separated by the embedding a-Al 2 O 3 matrix. The amorphous nature of both the Si nanostructured layers and the embedding a-Al 2 O 3 is evidenced in high resolution transmission electron microscopy images [3].…”
mentioning
confidence: 99%
“…On the other hand, amorphous nanostructures have been less studied due to the inherent difficulty to characterize them. Interestingly, it has been shown that they also show tunable optical band-gap properties [2] and are indeed very efficient sensitizers for RE ions [3]. Additionally, they can be produced following a low-cost low-temperature processes and it is expected a lower strain in the nanostructure embedded in the matrix due to their more flexible amorphous structure.In this work, we report our recent results on the design and synthesis of nanocomposite thin films based on Si or Ge amorphous nanostructures embedded in amorphous aluminum oxide (a-Al 2 O 3 ), labeled as a-Si:a-Al 2 O 3 and a-Ge:a-Al 2 O 3 , respectively.…”
mentioning
confidence: 99%